Professional work and austere healthcare in the UK: the case of physiotherapy - Tucker, Rachael Lelia (2023)
Following the 2008 global financial crisis, the UK government implemented austerity measures across the public sector to address the financial deficit. This had a significant impact on those working at the frontline of public sector services, including the National Health Service (NHS). Despite government assurances that the NHS would be protected, it has been hugely affected by austerity. Austerity and its associated logics, such as neoliberalism, have the potential to impact on how professions working in the NHS organise and exercise their professional work due to requirements to deliver cost efficiency savings and improve productivity. This thesis examines how one healthcare profession, physiotherapy, experiences and reconciles austerity in their daily professional work, using the neo-Weberian approaches to the sociology of professions as a theoretical framework. Analysis of the professions and how they reconcile logics that challenge traditional notions of professionalism thus far have focused on the archetypical and powerful profession of medicine. Whilst medicine has not been unaffected, the profession has arguably been able to maintain their position at the apex of the healthcare professional hierarchy when faced with challenges to professional work. Using semi-structured interviews and document analysis, this thesis examines how the physiotherapy profession, historically considered ‘subordinate’, negotiates challenges to their professional work. The findings suggest that whilst austerity is unspoken in NHS discourse and on the frontline, it has profoundly affected the organisation of the NHS and the professional work of physiotherapists. Physiotherapists worked (often at the detriment of their own health and wellbeing) to deliver patient care in resource-restricted settings. Bedside rationing became normalised and a focus on discharge out of hospital in some acute settings became organisational culture. Clinical reasoning and decision making in these settings was reconceptualised as resource-lead clinical reasoning. Patients’ rehabilitation potential was (often unknowingly) cognised with resources at the forefront, which demonstrated a changing notion of rehabilitation potential, driven by resource-lead clinical reasoning, to a concept of resource-contextualised rehabilitation potential. Professional elites undertook professionalising activities such as restratification and jurisdictional encroachment to extend physiotherapy's professional project, whilst rank and file members took on increasing levels of complexity, risk, and workload. Physiotherapists always had to negotiate power and hierarchy to practise their professional work and attempts to create change, resist measures, or improve services were often unsuccessful, leaving some feeling powerless. Some professional elites were able to use established networks with other (more powerful) professions or individuals to their advantage, whereas others experienced detrimental power imbalances, to the point of bullying and harassment. The role of physiotherapy had changed, becoming more focused on assessment and triage with subsequent delegation throughout the intraprofessional hierarchy. Physiotherapists interpreted a loss of meaningful work as a deconstruction of their professional identity, and thus, identity was reconstructed in contemporary healthcare settings. This led to some questioning the foundations of the profession entirely. Precarious work and dysfunctional employment practices were identified, something scarcely identified in other examinations of professional work. This thesis demonstrates how subordinated professions, such as physiotherapy, are more exposed to the harsh winds of austerity, and may be more vulnerable to precarious work practices. This thesis demonstrates how the legacy of subordinated professionalism lives on, impacting on how physiotherapists function and deliver care in contemporary healthcare. This has implications for not only physiotherapy’s future, but for that of other professions historically-considered subordinate, such as the allied health professions. These findings have implications for the sociology of professions literature and future research.